And then I was like, “No way!”: A variationist study of be like in young Cape Town speech - Horn, Elizabeth (School of African and GenderStuds, Anth and Ling, 2023)
Over the last two decades, the adoption of the quotative be like has emerged as one of the prominent examples of ongoing historical changes in English. This has been documented internationally, but the degree to which this change has taken place in South African English remains understudied. This dissertation conducts an apparent-time study of quotative systems in Cape Town. In this study, 1791 quotatives, collected from 64 sociolinguistic interviews, are analysed to assess the use of be like in contrast with older quotative verbs, as well as how the use of different quotatives is constrained by local social and linguistic variables. The judgement sample consists of young participants of four races, White, Coloured, Indian and Black, and a ‘control group' of older White speakers who represent the older norms. There is a focus on race in order to assess how social networks, and therefore language practices, may be deracialising, compared to the relative rigidities of a generation ago. Similarly, there is an emphasis on schooling in order to determine whether former model-C schools may be facilitating language practice change. A combination of statistical analyses in R, including ctrees and logistic regression, is used to determine the degree to which different social and linguistic variables influence quotative choice within the database. The results indicate that there is broad and prolific use of be like among the younger generation. Black and White participants use be like in the highest numbers, indicating that they may be leading the change. Similarly, speakers from former model-C schools use be like more than speakers from other schools, and best exhibit the content of quote and tense and temporal reference constraints on be like. Among them, there is a positive correlation between the use of be like and the expression of quotes containing internal monologue, as well as exclamations and non lexicalised sounds. Be like is also positively correlated with the use of historical present tense.